Natural bitumen stranding on the ocean beaches of Southern Australia: a historical and geospatial review. Issue 2 (2nd July 2016) - Edwards, Dianne S.; Vinall, Donald R.; Corrick, Alexander J.; McKirdy, David M.
ABSTRACT: The stranding of bitumen on ocean beaches in South Australia and western Victoria has been known for at least 170 years. In this review, we define what is meant by "coastal bitumen", illustrate its different varieties, and present the results of the first quantitative geospatial survey of its occurrence in South Australia. We then summarise the distinguishing molecular and isotopic characteristics of six families of these "ocean wanderer" bitumens, as pointers to their likely provenance. A bimonthly survey of six South Australian beaches conducted during 1991–1992 identified three categories of stranded petroleum: waxy bitumen, asphaltite and oil slicks. Each is physically and chemically distinct and bears no resemblance to any crude oil so far discovered in Australia's sedimentary basins. The maximum waxy bitumen loading of the beaches visited was 2 kg per 100 m. Accounting for 90% of the strandings, the waxy bitumens originate from oil seeps within the Indonesian Archipelago and are transported into southern Australian waters as flotsam by a complex system of surface ocean currents. The less common asphaltite is now understood to be a product of low-intensity seepage from tar mats exposed by the incision of submarine canyons into Australia's southern continental slope. The oil slicks represent occasional spillage from local maritime traffic. The stranding of petroleum along Australia's southern coastline therefore can be attributed to both natural and anthropogenic causes. The recent commencement of a new phase of oil and gas exploration in the Great Australian Bight highlights the need to characterise and quantify these inputs to the hydrocarbon loading of the adjacent ocean beaches.